2013
DOI: 10.1148/radiol.12121373
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Digital Mammography Alone and Digital Mammography Plus Tomosynthesis in a Population-based Screening Program

Abstract: The use of mammography plus tomosynthesis in a screening environment resulted in a significantly higher cancer detection rate and enabled the detection of more invasive cancers. Clinical trial registration no. NCT01248546.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

49
564
5
22

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 891 publications
(640 citation statements)
references
References 38 publications
49
564
5
22
Order By: Relevance
“…Newer studies point out that two DBT planes are not always necessary if MG has been performed in two planes [9]. Still DBT helps to improve diagnostic accuracy of detection of breast lesions compared to mammography alone [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Newer studies point out that two DBT planes are not always necessary if MG has been performed in two planes [9]. Still DBT helps to improve diagnostic accuracy of detection of breast lesions compared to mammography alone [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…As expected, the greatest gains in sensitivity were observed for younger women and those with heterogeneously dense breasts [36,37], but interestingly, there was no significant increase in cancer detection in those with extremely dense breasts [37]. DBT is currently being used in Australia as a diagnostic tool, but there is increasing evidence to suggest that it may be beneficial as a screening tool [33][34][35][36]. However, it is common practice to use DBT in conjunction with, rather than instead of, digital mammography, which results in a total examination dose approximately 2-3 times that of digital mammography alone.…”
Section: Advances In Technologymentioning
confidence: 56%
“…The main advantage of DBT is that it significantly reduces the effects of superimposition, thereby enabling visualisation of lesions that would be masked by over-or under-lying tissue and distinguishing real lesions from those mimicked by superimposition of normal structures [29]. A number of studies on large screening populations showed an increase in overall cancer detection rate and a reduction in recall rate when using DBT in addition to 2D digital mammography, compared to using 2D digital mammography alone [33][34][35][36]. As expected, the greatest gains in sensitivity were observed for younger women and those with heterogeneously dense breasts [36,37], but interestingly, there was no significant increase in cancer detection in those with extremely dense breasts [37].…”
Section: Advances In Technologymentioning
confidence: 99%
“…Newer technology such as digital breast tomosynthesis may provide higher sensitivity and increase cancer detection rate compared with digital mammography because of its ability to remove overlapping glandular tissue, the main reason for both false-positive and -negative results with traditional mammography. [10][11][12][13][14] Although tomosynthesis requires breast compression similar to mammogram, the compression force may be lower without affecting image quality. 14 Further studies would be helpful to determine whether the benefits of the MammoPad used by Chan et al 8 could have further benefit in tomosynthesis.…”
Section: Mammography For Breast Cancer Detection In Hong Kongmentioning
confidence: 99%